Effects of Alkoxy and Fluorine Atom Substitution of Donor Molecules on the Morphology and Photovoltaic Performance of All Small Molecule Organic Solar Cells - Qiu, Beibei; Chen, Shanshan; Xue, Lingwei; Sun, Chenkai; Li, Xiaojun; Zhang, Zhi-Guo; Yang, Changduk; Li, Yongfang (Frontiers in Chemistry, 2018)
Two benzothiadiazole (BT)-based small-molecule donors, SM-BT-2OR with alkoxy side chain and SM-BT-2F with fluorine atom substitution, were designed and synthesized for investigating the effect of the substituents on the photovoltaic performance of the donor molecules in all small molecule organic solar cells (SM-OSCs). Compared to SM-BT-2OR, the film of SM-BT-2F exhibited red-shifted absorption and deeper HOMO level of 5.36 eV. When blending with n-type organic semiconductor (n-OS) acceptor IDIC, the as-cast devices displayed similar PCE values of 2.33% and 2.76% for the SM-BT-2OR and SM-BT-2F-based devices, respectively. The SM-BT-2OR-based devices with thermal annealing (TA) at 120 oC for 10 min showed optimized PCE of 7.20%, however, the SM-BT-2F-based device displayed lower PCE after the TA treatment, which should be ascribed to the undesirable morphology and molecular orientation. Our results reveal that for the SM-OSCs, the substituent groups of small molecule donors have great impact on the film morphology, as well as the photovoltaic performance.